Pemberdayaan Masyarakat dalam Pembentukan dan Pengelolaan Bank Sampah dan Limbah Minyak Jelantah di RW 03 Kelurahan Medokan Semampir Kecamatan Sukolilo Kota Surabaya - Ratnaningsih Sri Yustini; Dyah Rini Prihastuty (Fakultas Teknik Universitas Cenderawasih, 2024)
Community empowerment in the formation and management of waste banks and used cooking oil waste in RW 03, Medokan Semampir Village, Sukolilo District, Surabaya City, aims to increase community awareness and participation in protecting the environment. This program was initiated as a response to the problem of solid and liquid waste which is often ignored, even though it has the potential to be managed into a resource with economic value. Through the waste bank, residents are involved in the process of managing household waste, sorting organic and inorganic waste, and utilizing it into valuable or recyclable items. Meanwhile, for used cooking oil waste, collection and education are carried out regarding the negative impacts of careless disposal of oil on the environment, as well as its use as raw material for biodiesel or other environmentally friendly products. The community empowerment approach is carried out through outreach, training and mentoring by the driving team. This program not only aims to improve the environment, but also opens up economic opportunities for local communities through a savings system from the sale of collected waste and used cooking oil. The results of this activity show an increase in environmental awareness among the community, as well as real economic benefits felt by the residents of RW 03.